Peran dan Fungsi Arsitektur Intelijen Bisnis Terhadap Pengambilan Keputusan Bisnis - Fauziah, Ananda; Fauzi, Achmad; Oktarini, Aliva Sofi; Wicaksono, Abdillah; Lazuardi, Ischaq; Armadani, Latifa Debby; Anwar, Muhammad Fachri; Komalasari, Sinta (Prisani Cendekia, 2024)
Apart from it’s value it has been recognized architectural Business Intelligence (BI) has an important influence in the business decision making process, Business intelligence architecture has a crucial role in determining progress in the business decision-making process, by using it, companies can collect, manage, analyze and present data efficiently. This research aims to determine the importance of the influence of business intelligence architecture in the business decision making process. According to theory, the maturity stage of Enterprise Architecture (EA) can influence the extent to which users can obtain appropriate BI representations, which in turn influences the effectiveness of business decision making. The research method used is a qualitative method with a literature review of journals. References made come from online journals such as Google Scholar. Methodological and consistent methods must be used in qualitative research. This study contributes to the BI architecture literature. Managerial findings will be useful for BI stakeholders in planning, reviewing and decision making.